Renal Transplantation in Highly Sensitized Patients: SIUT Experience. (July 2018) - Abbas, Khawar; Zafar, Mirza Naqi; Aziz, Tahir; Musharraf, Wajiha; Naqvi, Anwar; Rizvi, Adib
Abstract : Background: Sensitization to human leukocyte antigens remains a major barrier to successful renal transplantation. Material and Methods: Herein we describe our experience of seven highly sensitized patients with positive T-cell and B- cell lymphocytotoxicity crossmatch and T and B-cell flow crossmatch for IgG. All seven patients had donor specific antibodies (DSA) against HLA class I or class II antigens detected by Luminex single antigen beads assay (SAB).Desensitization protocol included 7-10 session of plasmapheresis, Low dose IVIgG, single dose of Rituximab and two doses of Bortezomib. Results: In all cases CDC and flow crossmatch were negative at the time of transplant. Three patients experienced rejection episode from 18 days to 3 months post-transplant. In a follow-up period of 2 to 12 months post -transplant all allografts are functioning well with mean serum creatinine is 1.25mg/dl. Conclusion: The early results of this study are encouraging. Protocols employed in the current study offer real hope to these patients unlikely to otherwise receive a kidney transplant.